RELIGIOUS CULTURE IN THE MODERN UKRAINIAN SOCIETY - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article deals with the formation of religious Culture in the Ukrainian society, justified the need for development of a culture of dialogue in interfaith relations.